MODIFIED DEINKING OF DIGITALLY PRINTED PAPER WITH WATER BASED INKJET INK - (:unkn) unknown (EDITURA ACAD ROMANE, 2017)
One of the most difficult recycling tasks is deinking of digitally printed paper with water based inkjet inks. The deinking of such paper is very important for the improvement of the digital printing industry. Generally, the manufacturers' preferred method is INGEDE Method 11p, which defines the universal deinking process. Based on this method, two different deinking procedures were assessed. The first was based on the standard procedure and standard chemicals of INGEDE method 11p, while the second followed the standard procedure of INGEDE method 11p, but with modified chemicals, applying soy-based oleic acid from soy oil. Using these deinking procedures, deinked papers with better optical properties were achieved. In addition to this, the second modified deinking procedure was also applied involving a different kind of bleaching agent, commercial bleach Oxi-Clean, which contains sodium percarbonate and sodium carbonate.
Keywords: inkjet; INGEDE; deinking; soy oleic acid